A stochastic overlapping generations real business cycle model of a small open economy - Kim, Kunhong (School of Management Working Papers, 1992)
A stochastic, discrete time version of Blanchard’s model of Perpetual Youth (Blanchard [1985]) is extended to an open economy with both tradable and nontradable goods. Some illustrative numerical simulations, based on parameter values taken from the existing real business cycle literature, are used to evaluate the comparative impact of productivity shocks on the tradable and nontradable goods sectors. It is shown that productivity shocks on the traded good sector leads to a positive correlation between aggregate output and the trade balance - aggregate output ratio. In contrast, productivity shocks on the non-traded good sector produces a negative correlation when the intertemporal elasticity of substitution between the current and future consumption is greater than the temporal elasticity of substitution between traded and non-traded good consumption.